PENERAPAN SENAM AEROBIC LOW IMPACT UNTUK MENGATASI KECEMASAN TERHADAP PASIEN DENGAN KELUHAN DAN GEJALA MENOPAUSE DI PUSKESMAS - Diana, Rika; Anggi Siska, Geuis; Ati Nurhayati, Nung (Yayasan Putra Sukamanah Sejahtera, 2026)
Menopausal is a natural phase in a woman’s life, by the end of the menstrual cycle and a decline in esterogen levels. While it is a biological process, it often brings with it a range of physical and emotional challenges, including anxiety, sexual dysfuntion, and sleep disturbances. In Indonesia, around 80% of women experience menopausal symptoms that significantly affect their quality of life especially in in areas such as the Cibeber public health center. This reality highlights the need for meaningful intervention to help menopausal women lead lives that are productive, independent, and fulfilling. The aim of this case study is to provide nursing care for a menopausal client, with a particular focus on the implementation of low-impact aerobic exercise as a therapeutic intervention to address common symtoms. This study used descriptive method grounded in the nursing care process, which includes assessment, diagnosis, planning, implementation, evaluation. The results of this case study revealed a noticeable reduction in menopausal symptoms especially anxiety and sexual dysfuntion after the client paraticipated in low-impact aerobic exercise for just four consecutive days. In conclusion, low-impact aerobic exercise has proven to be an effective non-pharmacological intervention for easing menopausal symtoms and improving clients overall quality of life. The author recommends low-impact aerobic exercise as a routine program, especially at the Cibeber Public Health Center, to prevent menopausal complaints and symtoms, thereby reducing the number of women experiencing menopausal symptoms.